Bivalent ligand UDCA-LPE inhibits pro-fibrogenic integrin signalling by inducing lipid raft-mediated internalization - Su, Jie; Gan-Schreier, Hongying; Goeppert, Benjamin; Chamulitrat, Walee; Stremmel, Wolfgang; Pathil-Warth, Anita (International journal of molecular sciences, 2018)
Ursodeoxycholyl lysophosphatidylethanolamide (UDCA-LPE) is a synthetic bile acid-phospholipid conjugate with profound hepatoprotective and anti-fibrogenic functions in vitro and in vivo. Herein, we aimed to demonstrate the inhibitory effects of UDCA-LPE on pro-fibrogenic integrin signalling. UDCA-LPE treatment of human embryonic liver cell line CL48 and primary human hepatic stellate cells induced a non-classical internalization of integrin β1 resulting in dephosphorylation and inhibition of SRC and focal adhesion kinase (FAK). Signalling analyses suggested that UDCA-LPE may act as a heterobivalent ligand for integrins and lysophospholipid receptor1 (LPAR1) and co-immunoprecipitation demonstrated the bridging effect of UDCA-LPE on integrin β1 and LPAR1. The disruption of either the UDCA-moiety binding to integrins by RGD-containing peptide GRGDSP or the LPE-moiety binding to LPAR1 by LPAR1 antagonist Ki16425 reversed inhibitory functions of UDCA-LPE. The lack of inhibitory functions of UDCA-PE and UDCA-LPE derivatives (14:0 and 12:0, LPE-moiety containing shorter fatty acid chain) as well as the consistency of the translocation of UDCA-LPE and integrins, which co-fractionated with LPE but not UDCA, suggested that the observed UDCA-LPE-induced translocation of integrins was mediated by LPE endocytic transport pathway.